High rate failure properties of human aortic tissue under longitudinal extension. (2018) - Gaur, Piyush; Verma, Khyati; Chawla, Anoop; Mukherjee, Sudipto; Lalwani, Sanjeev; Malhotra, Rajesh; Mayer, Christian; Ghosh, Pronoy; Chitteti, Ravi Kiran
Understanding the failure properties of human aortic tissue at high strain rate loading is important to understand the mechanism of traumatic rupture of aorta (TRA). This study reports 18 uniaxial tensile tests performed on human aortic tissue in the longitudinal direction. Rectangular specimens were obtained from cadaveric human aortic tissue. Uniaxial tensile tests were performed at target strain rates of 0.001 s –1, 65 s –1, 130 s –1 and 190 s –1 to failure. High-speed video was used to measure the gripper to gripper displacement. Failure stress and strain were calculated. The load-deformation relationship of aorta is found to be nonlinear and strain rate dependent with higher failure stress and lower effective failure engineering strains at higher strain rates. Across tests, the failure stress ranged from 0.86 MPa to 1.86 MPa and effective failure strain from 13.52% to 10.80%.